A Framework to Estimate Local Atmospheric Densities With Reduced Drag‐Coefficient Biases. Issue 3 (9th March 2022) - Ray, Vishal; Scheeres, Daniel J.; Alnaqbi, Suood; Tobiska, W. Kent; Hesar, Siamak G.
Abstract: An accurate estimation of upper atmospheric densities is crucial for precise orbit determination (POD), prediction of low Earth orbit satellites, and scientific studies of the Earth's atmosphere. But densities estimated using satellite tracking data are always uncertain up to the drag‐coefficient assumed in the inversion method. This work develops a new framework to simultaneously estimate the density and drag‐coefficient for satellites with a time‐varying attitude. We do so by leveraging Fourier drag‐coefficient models, previously developed by the authors, and physical models of the drag‐coefficient. The method is tested with synthetic data for different geomagnetic activities, altitude levels, and errors in the gas‐surface interaction parameters. We report an improvement of up to 70% in density estimates for the simulations. Finally, POD data from Spire satellites are used for validation. An improvement of around 29% is obtained in the filter density estimates over NRLMSISE‐00 and 49% over JB2008 compared to the High Accuracy Satellite Drag Model densities. Plain Language Summary: With the rapidly increasing number of Earth‐orbiting satellites, accurate monitoring of the satellite positions has become crucial for collision avoidance purposes. One of the major sources of error in the tracking of LEO satellites is the force that the tenuous atmosphere exerts on satellites, known as atmospheric drag. Modeling the drag force is complicated due to the uncertainties in the atmospheric density and the drag‐coefficient—a parameter that governs the interactions between the atmosphere and the satellite surface. In this work, we propose a method to obtain corrections to both the density and the drag‐coefficient from satellite tracking data, thus improving the tracking accuracy in the process. Key Points: We provide a new method to estimate accurate local atmospheric densities at sub‐orbital cadence The biases in density and drag‐coefficient are decorrelated using time‐variations induced due to attitude variations in the latter The reduction in density bias is validated using Precision Orbit Determination data from Spire satellites